Neutron Scattering - Alfredo Monteiro, Waldemar (IntechOpen, 2016)
This book brings suitable data concerning theory and experiments of neutron interactions with different materials. Since the neutron discovery by Chadwick in 1932, researchers of the entire world begin to make studies about it. It is well known that neutron have no charge, and their electric dipole moment is either zero or too small to measure, but theories and experiments show that neutron has spin (presence of magnetic moment), and polarization neutron scattering is plausible. The reader can obtain remarks about inelastic scattering cross sections for neutron; polarized neutron reflectivity; scattering methods; neutron reflectometry tool to probe the chemical structures; neutron scattering for amino acid crystals; and small-angle neutron scattering nanoemulsion heat transfer fluids in this book.